The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/gcb.12710
|View full text |Cite
|
Sign up to set email alerts
|

Strong topographic sheltering effects lead to spatially complex treeline advance and increased forest density in a subtropical mountain region

Abstract: Altitudinal treelines are typically temperature limited such that increasing temperatures linked to global climate change are causing upslope shifts of treelines worldwide. While such elevational increases are readily predicted based on shifting isotherms, at the regional level the realized response is often much more complex, with topography and local environmental conditions playing an important modifying role. Here, we used repeated aerial photographs in combination with forest inventory data to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 69 publications
6
47
0
3
Order By: Relevance
“…This result agrees with a larger‐scale study of patterns of adult trees in the same region (Greenwood et al. ), and also with other studies of establishment patterns and treeline dynamics (Resler et al. ; Holtmeier & Broll , ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result agrees with a larger‐scale study of patterns of adult trees in the same region (Greenwood et al. ), and also with other studies of establishment patterns and treeline dynamics (Resler et al. ; Holtmeier & Broll , ).…”
Section: Discussionsupporting
confidence: 92%
“…Remote sensing analyses have demonstrated the importance of shelter for treeline form and advance on a large scale (Greenwood et al. ), and here we have identified the microsite‐scale processes that influence these regional patterns; seedlings will establish more successfully, and treeline will thus advance further, in sites that offer some degree of topographic shelter.…”
Section: Discussionmentioning
confidence: 65%
“…Following Harsch & Bader () and Greenwood et al . (), local patterns of tree line advance in the Central Mountain Range of Taiwan can be classified as abrupt advancing (tree lines advancing at high density over short distances), diffuse advancing (tree lines advancing at low density over longer distances) and static (tree lines that are not advancing), and of these, the authors have shown that the diffuse form is advancing most rapidly in the Hehuanshan area (Greenwood et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…The A. kawakamii forest is advancing upward in altitude on Hehuanshan in a complex and topographically mediated way, with considerable spatial variation (Greenwood et al ., , ). Following Harsch & Bader () and Greenwood et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation